Patient satisfaction following root canal treatment by undergraduate and postgraduate dental students: A comparative questionnaire study - Ocak, Mevlüt Sinan; Konuş, Furkan; Öztekin, Faruk (Turkish Endodontic Society, 2026)
Purpose: This study aimed to evaluate patient satisfaction following root canal treatment performed by undergraduate and postgraduate dental students. Methods: A total of 120 patients were included (n=60 per group). A validated questionnaire was used, consisting of socio-demographic questions and eight satisfaction items scored on a 5-point Likert scale. Statistical analyses were performed using non-parametric tests, with significance set at p<0.05. Results: No significant differences were found between the groups regarding socio-demographic variables (p>0.05). However, overall satisfaction scores were significantly higher among patients treated by postgraduate students (p=0.001). In the undergraduate group, differences were observed according to age and marital status, with some results only marginally significant (p?0.04). Patients with lower income reported greater satisfaction with treatment plan explanations (p=0.027). Conclusion: Both groups received generally favorable satisfaction ratings; however, postgraduate students obtained significantly higher scores. In the undergraduate group, socio-demographic factors, particularly age and marital status, appeared to influence satisfaction levels. Overall, these findings suggest potential areas for improvement in dental education and clinical supervision, including strategies to enhance patient-centered care. © 2026, Turkish Endodontic Society. All rights reserved.
Keywords: Dental education; patient satisfaction; root canal therapy; students